Altering Perceived Context: Transportation Cues Influence Novelty-Induced Context Exploration - Nemchek, Victoria; Agee, Laura A.; Malone, Cassidy A.; Raskin, Marissa; Seese, Sydney; Monfils, Marie H. (Frontiers in Behavioral Neuroscience, 2021)
Context is the milieu in which everything occurs. Many research studies consider context, or even explicitly manipulate it; yet it remains challenging to characterize. We know that a context surrounds and influences tasks; however, the boundaries of its influence are difficult to define. In behavioral science, context is often operationalized by the physical environment in which the experiment takes place, and the boundaries of the context are assumed to begin at the entrance to that the room or apparatus. Experiences during transportation to the testing space have been shown to impact rodent behavior and memory, but transportation’s relationship with novelty and physical environment is not fully understood. The current study explored how familiar vs. novel cues, both within a physical environment and preceding it, impact perception of a context. We manipulated context on 3 levels: physical testing environment, object cues within that environment, and transportation cues preceding entrance to the testing environment. We found that novel transportation cues can change rats’ perception of both familiar and novel contexts. The effects of transportation on perceived context may be affected by the length of the retention interval, testing environment, and behavioral range. These data suggest that context is a broad concept that include cues across time and is sensitive to small differences in experience.